2007
DOI: 10.1371/journal.pone.0000297
|View full text |Cite
|
Sign up to set email alerts
|

Bats Avoid Radar Installations: Could Electromagnetic Fields Deter Bats from Colliding with Wind Turbines?

Abstract: Large numbers of bats are killed by collisions with wind turbines, and there is at present no direct method of reducing or preventing this mortality. We therefore determine whether the electromagnetic radiation associated with radar installations can elicit an aversive behavioural response in foraging bats. Four civil air traffic control (ATC) radar stations, three military ATC radars and three weather radars were selected, each surrounded by heterogeneous habitat. Three sampling points matched for habitat typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Baerwald and Barclay (2009) relate intensity of bat activity to geographic variation in the number of bat fatalities in order to predict which locations for wind turbines would be less harmful for bat populations. Nicholls and Racey (2007) recently suggested the use of electromagnetic emissions to reduce bat fatalities at wind turbines after observing reduced bat activity in the vicinities of a strong electromagnetic field. The great responsiveness of the scientific community toward the escalating problem of bat fatalities at wind turbines will, we hope, bring about an effective method of preventing these fatalities without hindering our efforts to slow global warming.…”
Section: The Fate Of Migratory Bats In a Changing Worldmentioning
confidence: 99%
“…Baerwald and Barclay (2009) relate intensity of bat activity to geographic variation in the number of bat fatalities in order to predict which locations for wind turbines would be less harmful for bat populations. Nicholls and Racey (2007) recently suggested the use of electromagnetic emissions to reduce bat fatalities at wind turbines after observing reduced bat activity in the vicinities of a strong electromagnetic field. The great responsiveness of the scientific community toward the escalating problem of bat fatalities at wind turbines will, we hope, bring about an effective method of preventing these fatalities without hindering our efforts to slow global warming.…”
Section: The Fate Of Migratory Bats In a Changing Worldmentioning
confidence: 99%
“…Some species may be assessing them as potential roost sites (Cryan 2008), however there is also some evidence of foraging behaviour around turbines (Horn et al 2008;Ahlén 2004). Bats tend to be concentrated in areas of high insect density (Nicholls and Racey 2007) and are much more likely to begin hunting when large numbers of insects are congregating (Griffin et al 1960). Reports into bat-turbine interactions frequently state the importance of investigation into the possibility of insect attraction to turbines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Reports into bat-turbine interactions frequently state the importance of investigation into the possibility of insect attraction to turbines (e.g. Johnson and Kunz 2004;Ahlén 2004;Nicholls and Racey 2007;Rodrigues et al 2006), particularly since the recent loss of feeding habitats may be pressuring bats to feed in alternative areas (Wickramasinghe et al 2003). Turbine colour may play an important part in insect attraction (Ahlén 2004), although to date this has not been closely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[22] also reported anecdotal evidence that bats foraging offshore in Sweden avoided an area around Utgrunden lighthouse where a powerful radar was in permanent operation. However, although it has been demonstrated that large air traffic control and weather radars appear to exert an aversive response on foraging bats [21], this has little practical application in preventing bats from colliding with turbine blades. It is therefore necessary to establish whether a deterrent effect can be replicated with a small, portable radar system.…”
Section: Introductionmentioning
confidence: 99%